FORMULATION DEVELOPMENT AND EVALUATION OF SOLID SELF MICROEMULSIFYING DRUG DELIVERY SYSTEM OF AZELNIDIPINE (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
This study aimed to develop a self-micro emulsifying drug delivery system (SMEDDS) for poorly soluble azelnidipine using Capryol 90 as the oil, Tween 80 as the surfactant, and transcutol-HP as the co-surfactant. A factorial design was used to optimize the formulation, and Neusilin UFL2 was used as an adsorbent to convert the liquid SMEDDS to solid SMEDDS. The optimized formulation had a particle size of 80.5nm, a transmittance of 98.2%, a zeta potential of -3.1 mV, and a polydispersibility index of 0.226. The solid SMEDDS tablet exhibited improved drug release (99.4% in 60 minutes) compared to the marketed tablet (67.09.75%) and pure drug (26.17%). This study demonstrates the potential of the SMEDDS approach to enhance the solubility and in-vitro drug release of poorly soluble drugs such as azelnidipine.